Synthesis and Characterization Molecularly Imprinted Polymers for Analysis of Dimethylamylamine Using Acrylamide as Monomer Functional - Amin, Saeful; Damayanti, Sophi; Ibrahim, Slamet (Jurnal Kefarmasian Indonesia, 2018)
A selective separation techniques with Molecularly Imprinted Polymer (MIP) for High-Performance Liquid Chromatography (HPLC) has been developed for the assay of Dimethylamylamine (DMAA) doping compounds. Molecular imprinted polymer (MIP) is a technique to produce a polymer having the cavity due to the disposal of the templates, in which the cavity serves to recognize the molecules of the same size, structure, chemical and physical properties. The selectivity and affinity of the templates itself will increase, while the concentration value is increasing. MIP is made by DMAA as template, acrylamide as functional monomer, ethylene glycol dimethacrylate (EGDMA) as cross linking, azobisisobutyronitrile (AIBN) as the initiator and chloroform as a porogen solvent; using bulk method. The aim of research are conduct the MIP for the DMAA compound analysis, then the formed MIP is characterized by using Fourier Transform Infra Red (FTIR) and Scanning Electron Microscopy (SEM) to find out the polymer complexes formed and the morphological form of the MIP. The MIP formed then was analyzed by using High-Performance Liquid Chromatography (HPLC) to know the amount of the DMAA, the adsorption capacity, and the adsorption condition found in the MIP. The result of analysis on the content of DMAA in the MIP by using UV-Vis Spectrophotometer is 1.957 mg. Scanning Electron Microscopy (SEM) shows that the MIP has irregular and rough morphological structure; while the NIP has irregular morphology structures and smooth surfaces shape